Pliometría como herramienta para mejorar fuerza muscular en miembros inferiores posterior a esguince de tobillo grado 1 en futbolistas categoría sub 15 de la Federación Deportiva de Chimborazo, 2017 – 2018. - Alvarez Maigualema, Fernando Daniel (2019)
This research work allowed to know a more about the technique of plyometric as a tool to improve muscle strength in lower limbs after ankle sprain in degree 1 in soccer players of the Sports Federation of Chimborazo. Within this investigation, it was possible to verify that it had a positive contribution within the expected results to be obtained and had a good reaction from the members of the Sports Federation of Chimborazo especially for theirs players who have suffered from ankle sprains from their daily work as athletes. However, thanks to the application of plyometric (plyometrics exercises) in ankle sprains grade 1, muscle strength improvement was observed. The applied research at a given time and in a duration field, a series of plyometric exercises was used in a specific duration time for the soccer players of the Sports Federation of Chimborazo. This research had a favorable impact for young players.